Treatment and practical considerations of diabetic kidney disease - Bilen, Yara; Almoushref, Allaa; Alkwatli, Kenda; Osman, Omar; Mehdi, Ali; Sawaf, Hanny (Frontiers in Medicine, 2023)
Diabetics kidney disease (DKD) is a complication of diabetes that can lead to kidney failure. Over the years, several drugs have been developed to combat this disease. In the early nineties, angiotensin blockade (ACEi and ARBs) was introduced which revolutionized the treatment of DKD. In recent years, newer drugs such as sodium-glucose co-transporter 2 (SGLT2) inhibitors, glucagon-like peptide-1 (GLP-1) receptor agonists, endothelin antagonists and mineralocorticoid receptor antagonists (MRA) have shown great promise in reducing albuminuria and protecting the kidneys. These drugs are being used in combination with lifestyle modifications, patient education, and risk factor modification to effectively manage DKD. In this review, we will explore the latest pharmacological options, their efficacy, and their potential to revolutionize the management of this debilitating disease.